Comparison of Wolbachia Bacterial Density in Females of Four Thelythokous Strains of Trichogramma cordubensis and T. evanescens (Hymenoptera, Trichogrammatidae) - Pascal, C.; Pintureau, B.; Katchadourian, C.; Grenier, S.; Bolland, P.; Robin, C.; Vallier, A. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2006)
The endosymbionts of the genus Wolbachia infect numerous arthropods and nematods, and often cause different effects on the reproduction of these hosts. The endosymbiotic bacteria Wolbachia induces the thelytokous mode of reproduction in the egg parasitoids of the genus Trichogramma. The Dot-blot technique was performed to compare the symbiont Wolbachia density using the wsp gene of Wolbachia and the 18S gene of Trichogramma. It was established that Wolbachia density is not different in two host species, Trichogramma cordubensis Vargas et Cabello and T. evanescens Haliday.